Redox switching and oxygen evolution electrocatalysis in polymeric iron oxyhydroxide films - LYONS, MICHAEL EDWARD (Royal Scoety of Chemistry, 2009)
Outstanding issues regarding the redox switching characteristics and the oxygen evolution reaction (OER) electrocatalytic behaviour of multicycled iron oxyhydroxide films in aqueous alkaline solution have been examined. Charge percolation through the hydrous layer has been quantified, using cyclic voltammetry, in terms of a charge transport diffusion coefficient DCT which admits a value of ca. 3 ? 10-10 cm2 s-1. Steady-state Tafel plot analysis and electrochemical impedance spectroscopy have been used to elucidate the kinetics and mechanism of oxygen evolution. Tafel slope values of ca. 60 mV dec-1 and ca. 120 mV dec-1 are found at low and high overpotentials respectively, whereas the reaction order with respect to hydroxide ion activity changes from ca. 3/2 to ca. 1 as the potential is increased. These observations are rationalised in terms of a kinetic scheme involving Temkin adsorption and the rate determining formation of a physisorbed hydrogen peroxide intermediate on the oxide surface. The dual Tafel slope behaviour is ascribed to the potential dependence of the surface coverage of adsorbed intermediates.
PUBLISHED
Keywords: Chemistry